ANALISIS TINGKAT AKURASI MODEL-MODEL PREDIKSI KEBANGKRUTAN UNTUK MEMPREDIKSI VOLUNTARY AUDITOR SWITCHING (Studi pada perusahaan manufaktur yang terdaftar di BEI) - Jayanti, Queenaria; Rustiana, Rustiana (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2015)
The aim of the study is to test the degree of accuracy of bankruptcy prediction modelsÃ‚Â to predict voluntary auditor switching, and at the same time the study also examinesÃ‚Â differencetiation in accuracy among the models. In this study, five bankruptcy predictionmodels are used, the model consist of Altman ZÃ¢â‚¬Â-Score modification, Olson Y-score,Ã‚Â Zmijewski X-Score, G-Score Grover, and Springate S-Score.The study consist of 432 companies are listing on Indonesia Stock Exchange duringÃ‚Â the years 2008-2011. The data are drawn from the Annual Financial Statements, IDXÃ‚Â Fact Book, and the Indonesian Capital Market Directory. The hypothesis is examined byÃ‚Â One Way ANOVA with level of significance 5%.Ã‚Â The results indicate no differencing between the accuracy of bankruptcy predictionÃ‚Â among the models in predict the company undertake voluntary decision of switchingÃ‚Â auditors. However, the result shows that models Grover G - Score is the most high inÃ‚Â predicting of accuracy ratings. The implication of this study is for auditor to consider theÃ‚Â model to design the substantif test in audit activities.Ã‚Â Keywords: Altman ZÃ¢â‚¬Â-Score modification, Ohlson Y-Score, Zmijewski X-Score, G-ScoreÃ‚Â Grover, Springate S-Score, voluntary switching auditors.